2017
DOI: 10.1039/c7cc08430g
|View full text |Cite
|
Sign up to set email alerts
|

An acyclic zincagermylene: rapid activation of dihydrogen at sub-ambient temperature

Abstract: The first example of a stable zincagermylene, :Ge(TBoN)(ZnL*) (TBoN = N(SiMe){B(DipNCH)}, Dip = CHPr-2,6; L* = -N{CH[C(H)Ph]Me-2,6,4}(SiPr)) is prepared and shown to have unprecedented reactivity for a germylene, with respect to the activation of dihydrogen. Computational analyses point towards this being partially derived from the electron releasing nature of the amido-zinc fragment, which leads to a narrowing of the HOMO-LUMO gap in the compound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…So as to demonstrate a degree of generality to the accessibility of 1,2-dizincioorganyls, compound 9 was treated with two equivalents of the bulky amido zinc halide, [ TBo LZnBr(THF)] ( TBo L = –N(SiMe 3 ){B(DipNCH) 2 }),18 which led to colourless crystalline 11 in good isolated yield (Scheme 3). Compound 11 is the first structurally characterised example of a 1,2-dizincioethene, and differs from 10 in that it incorporates a boryl substituted amide ligand, which is less bulky than the L* amide in 10 , but which we have previously exploited in the kinetic stabilisation of low oxidation state main group compounds 19. Compounds 10 and 11 are thermally stable in both solution and the solid state.…”
Section: Resultsmentioning
confidence: 99%
“…So as to demonstrate a degree of generality to the accessibility of 1,2-dizincioorganyls, compound 9 was treated with two equivalents of the bulky amido zinc halide, [ TBo LZnBr(THF)] ( TBo L = –N(SiMe 3 ){B(DipNCH) 2 }),18 which led to colourless crystalline 11 in good isolated yield (Scheme 3). Compound 11 is the first structurally characterised example of a 1,2-dizincioethene, and differs from 10 in that it incorporates a boryl substituted amide ligand, which is less bulky than the L* amide in 10 , but which we have previously exploited in the kinetic stabilisation of low oxidation state main group compounds 19. Compounds 10 and 11 are thermally stable in both solution and the solid state.…”
Section: Resultsmentioning
confidence: 99%
“…[37][38][39][40][41][42][43][44][45] Jones has also used the boryl fragment as a constituent of bulky amido ligands. 46,47 Trzaskowski and coworkers carried out theoretical studies comparing the second-generation Grubbs-Hoveyda catalyst, which bears an NHC ligand, to an analogue featuring an anionic N-heterocyclic boryl (NHB) ligand in place of the NHC. 48,49 With the NHB analogue there is a substantial increase in the Ru-O bond distance of the trans ether ligand, and a decrease in energy for the dissociation of the ether, which is attributed to the increased σ-donation of the NHB in comparison with the NHC.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Sasamori et al reported on a redox‐active bis(ferrocenyl)germylene and its reactivity . Furthermore, Jones, Frenking , and co‐workers described the first example of a stable zincagermylene, which has been shown to have unprecedented reactivity for a germylene, with respect to the activation of dihydrogen …”
Section: Introductionmentioning
confidence: 99%